MUKJIZAT NARATOLOGIS: STUDI ANDRAGOGI ATAS KISAH MUSA-KHIDR DALAM SURAH AL-KAHFI 60-82 - Nurul Azizeh (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2019)
This study wants to explore the story of Prophet Moses and Khidr as figures of adult education in the perspective of Islamic education. The main issue of this study is how the concept of adult education in the perspective of Islamic education is able to increase the spectrum space of andragogical education. By using content analysis and narrative approaches that are primarily sourced QS. al-Kahfi: 60-82, this study seeks to show the values of Islamic education that are based on the theory of andragogical education. The characterization of Moses and Khidr as a figure of andragogical education is: Moses is present as the subject of andragogical education which has a sense of curiosity and Khidr as an object, a figure who has ladunni knowledge and high spiritual abilities. Through the method of lecture, discussion and demonstration, Musa-Khidr's narrative dialogue shows adult learning that contains the values of Islamic education, namely the moral value between teacher and student and morality in learning. The implication of this paper is an effort to contribute to scientific repertoire in the world of education as one of the dimensions of the naratological miracles of the Qoran.